Interest Groups and Political Development in Turkey - Bianchi, Robert (Book collections on Project MUSE., 2014)
This book shows that governmental efforts to expand corporatism in the major occupational associations intensified conflict in and between socioeconomic sectors, encouraged militancy from disaffected group leaders, and promoted polarization between pluralist and corporatist associations. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these importan.